National dengue surveillance in Cambodia 1980-2008: epidemiological and virological trends and the impact of vector control - Rekol Huy; Philippe Buchy; Anne Conan; Chantha Ngan; Sivuth Ong; Rabia Ali; Veasna Duong; Sunnara Yit; Sophal Ung; Vantha Te; Norith Chroeung; Nguon Chan Pheaktra; et al. (The World Health Organization, 2010)
OBJECTIVE: Dengue has been reportable in Cambodia since 1980. Virological surveillance began in 2000 and sentinel surveillance was established at six hospitals in 2001. Currently, national surveillance comprises passive and active data collection and reporting on hospitalized children aged 0-15 years. This report summarizes surveillance data collected since 1980. METHODS: Crude data for 1980-2001 are presented, while data from 2002-2008 are used to describe disease trends and the effect of vector control interventions. Trends in dengue incidence were analysed using the Prais-Winsten generalized linear regression model for time series. FINDINGS: During 1980-2001, epidemics occurred in cycles of 3-4 years, with the cycles subsequently becoming less prominent. For 2002-2008 data, linear regression analysis detected no significant trend in the annual reported age-adjusted incidence of dengue (incidence range: 0.7-3.0 per 1000 population). The incidence declined in 2.7% of the 185 districts studied, was unchanged in 86.2% and increased in 9.6%. The age-specific incidence was highest in infants aged <1 year and children aged 4-6 years. The incidence was higher during rainy seasons. All four dengue virus (DENV) serotypes were permanently in circulation, though the predominant serotype has alternated between DENV-3 and DENV-2 since 2000. Although larvicide has been distributed in 94 districts since 2002, logistic regression analysis showed no association between the intervention and dengue incidence. CONCLUSION: The dengue burden remained high among young children in Cambodia, which reflects intense transmission. The national vector control programme appeared to have little impact on disease incidence.